Flow cytometric enumeration of Plasmodium berghei-infected red blood cells stained with SYBR Green I - Voravuth Somsak (2018)
High-throughput methods for evaluation of in vivo efficacy of candidate compounds against Plasmodium parasites are necessary during the antimalarial drug development process. It is essential that enumeration of parasitemia in the infected blood from experimental host animals is accurate and reliable. Flow cytometric enumeration of parasitized cells stained with fluorescent dye is a rapid alternative method to conventional microscopic counting. In this study, a protocol for flow cytometric enumeration of rodent malaria parasite Plasmodium berghei-infected red blood cells (RBC) stained with SYBR Green I was developed. The optimal concentration of SYBR Green I used to stain infected RBC was 4× for 30min. This SYBR Green I staining protocol in combination with the bi-dimensional FL-1530/FL-3620detection method accurately detects parasitemia above 0.02%. The dye is stable during the prolonged incubation period necessary for accurate enumeration of parasitemia, with no loss of fluorescent signal over a period of hours. This protocol was validated in an antimalarial assay and the result was comparable to that obtained from conventional microscopic counting. The SYBR Green I flow cytometric protocol is thus a rapid and precise tool for high-throughput in vivo antimalarial drug screening. © 2011 Elsevier B.V.